Study On The Efficacy Of Hydrotherapy For Katigraha In Elderly Population - Mahajan, Manish; Patwardhan, R P (International Research Journal of Ayurveda & Yoga, 2020)
Katigraha is a common complaint encountered in every stratum of society, occupation, and racial groups. It is widely prevalent in these days due to sedentary living habits and hazardous work patterns. In Ayurvedic literature we find references regarding Katishoola, Trikashola, Trikavedana, Katigraha. In which pain in the low back region forms the main symptom, depending upon the involved area. Hydrotherapy is one of the oldest known therapies. Sebastian Kneipp(1821-97)4 believed that water is having the property to dissolve, strengthen and removes the diseased matter from the body and strengthen the body by restoring cleansed blood to the tissues. So by using water in different treatment procedures, one can help to remove the toxic material and to get maximum circulation to that particular area. Hence for treating Katigraha water is used to remove the toxic material and to get maximum circulation to that particular area. By which we can relive the spasm of muscles and the main symptoms of Katigraha which includes restricted spinal movements. This paper reports randomised clinical study evaluating the effect of hydrotherapy. The selected patients were thoroughly examined subjectively, detailed general history and physical examination findings were noted. Hydrotherapy has a significant effect in reduction of ruja, and different movements flexion, extension, left and right lateral movements.